Effect of laboratory aging on the performance of asphalt mixture containing high RAP content with the rejuvenator-loaded fiber - Yuxuan Sun; Fan Zhang; Augusto Cannone Falchetto; Di Wang (Case Studies in Construction Materials)
This study investigates the performance of recycled asphalt mixtures containing 50 % reclaimed asphalt pavement (RAP), focusing on the impact of rejuvenator-loaded fibers under various aging conditions: short-term aging (STA) and long-term aging at four (LTA4) and seven (LTA7) days. The mixtures were compared to a standard virgin AB16 asphalt mixture and an AB16 mixture with 50 % RAP rejuvenated with a soft binder. The evaluation included water sensitivity tests, studded tire abrasion tests, dynamic modulus tests, and indirect tensile fatigue tests. Finally, an Environmental Scanning Electron Microscope (ESEM) was utilized to analyze the distribution and action mechanisms of rejuvenator-loaded fibers within the asphalt mixture. Research results showed that aging improved indirect tensile strength (ITS) and dynamic modulus across asphalt mixtures. Rejuvenator-loaded fibers could enhance ITS values, stabilize the indirect tensile strength ratio (ITSR), and improve structural strength. Analysis of the fracture surface morphology revealed that these fibers were well dispersed and exhibited significant bridging effects within the mixture. However, these fibers reduced abrasion resistance over time. While initially beneficial, their effectiveness in prolonging fatigue life declined with extended aging, though they still mitigated deterioration under high stress.